2015
DOI: 10.5229/jecst.2015.6.2.35
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Polymeric Binders for Silicon Anodes in Lithium-Ion Batteries

Abstract: Advanced polymeric binders with unique functions such as improvements in the electronic conduction network, mechanical adhesion, and mechanical durability during cycling have recently gained an increasing amount of attention as a promising means of creating high-performance silicon (Si) anodes in lithium-ion batteries with high energy density levels. In this review, we describe the key challenges of Si anodes, particularly highlighting the recent progress in the area of polymeric binders for Si anodes in cells. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…Preparation of Si anodes from a high viscoelasticity of SA/Ca gel as slurry, lead to a high coulombic efficiency during the lithiation/delithiation process of Si anodes, even by cycle numbers of 70. Similar trends are reviewed also in Reference .…”
Section: Efforts To Enhance the Si Electrode Stabilitysupporting
confidence: 59%
See 2 more Smart Citations
“…Preparation of Si anodes from a high viscoelasticity of SA/Ca gel as slurry, lead to a high coulombic efficiency during the lithiation/delithiation process of Si anodes, even by cycle numbers of 70. Similar trends are reviewed also in Reference .…”
Section: Efforts To Enhance the Si Electrode Stabilitysupporting
confidence: 59%
“…Polymer binder for Si has also to fulfill some requirements such as; Advanced mechanical properties to avoid cracks Improved dispersivity for Si and carbon additives Improved adhesion on Cu electrode Li + ion transport ability …”
Section: Efforts To Enhance the Si Electrode Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The paint manufacturing industry is historically one of the major investors in the development of new polymeric binders in order to improve the cohesion of pigment particles and adhesion to the coated substrate following evaporation of the solvent [1][2][3]. The electronics industry uses binders to improve the conductivity and mechanical strength of electrodes in batteries [4][5][6]. Binders are also used in rocket manufacturing to improve the safety and ballistic performance of propellants [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it will be beneficial to develop binders that can be processed with less toxic, or even non-toxic solvents. Recently, it was reported that water-based binder such as styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) effectively improves the cycling stability of silicon electrode [15][16][17][18][19][20][21][22][23][24][25][26] . According to a previous report by Hochgatterer et al [21] , the formation of a covalent chemical bond between the CMC and silicon particle plays an important role in the effective binding and improved performance.…”
Section: Introductionmentioning
confidence: 99%